Konselor Sekolah dalam Mengembangkan Karakter Siswa Selama Covid-19 - Slameto, Slameto (Sekolah Tinggi Teologi Simpson Ungaran, 2021)
Like other educators, school counselors initially responded to the Covid-19 crisis with confusion and uncertainty, for which they needed solutions with collaboration and innovation. In schools with a framework used to focus on the 'whole child.' MTSS supports academic growth and achievement, but also supports many other areas. MTSS is a holistic learning approach to support students through large-scale life changes due to the global pandemic. The pandemic is prompting school counselors to turn to virtual tools to engage with and track students and families. School counselors make use of certain technological tools, but also offer some caveats about their use. During the pandemic, school counselors are expected to provide comprehensive services to students and families, and instead step into a leadership role that allows them to provide comprehensive virtual social-emotional and academic learning in counseling services to their students. The need for school counselors to stay connected to students during COVID-19 through providing virtual advice, providing virtual counseling (individual and/or group): trauma care, cyberbullying, managing expectations, paying attention to burnout, and managing burnout. For the future of students, meet students wherever they are while respecting digital security, cyberbullying, and protecting student privacy, and taking care to ensure confidentiality.